Ethylene-regulated immature fruit abscission is associated with higher expression of CoACO genes in Camellia oleifera. Issue 6 (2nd June 2021) - Hu, Xiao; Yang, Mi; Gong, Shoufu; Li, Hongbo; Zhang, Jian; Sajjad, Muhammad; Ma, Xiaoling; Yuan, Deyi
Abstract : Immature fruit abscission is a key limiting factor in Camellia oleifera Abel. ( C. oleifera ) yield. Ethylene is considered to be an important phytohormone in regulating fruit abscission. However, the molecular mechanism of ethylene in regulating fruit abscission in C. oleifera has not yet been studied. Here, we found that the 1-aminocyclopropane-1-carboxylic acid (ACC) content was significantly increased in the abscission zones (AZs) of abnormal fruits (AF) which were about to abscise when compared with normal fruits (NF) in C. oleifera 'Huashuo'. Furthermore, exogenous ethephon treatment stimulated fruit abscission. The cumulative rates of fruit abscission in ethephon-treated fruits (ETH-F) on the 4th (35.0%), 8th (48.7%) and 16th (57.7%) days after treatment (DAT) were significantly higher than the control. The ACC content and 1-aminocyclopropane-1-carboxylate oxidase (ACO) activity in AZs of ETH-F were also significantly increased when compared with NF on the 4th and 8th DAT. CoACO1 and CoACO2 were isolated in C. oleifera for the first time. The expressions of CoACO1 and CoACO2 were considerably upregulated in AZs of AF and ETH-F. This study suggested that ethylene played an important role in immature fruit abscission of C. oleifera and the two CoACOs were the critical genes involved in ethylene's regulatory role.